THE EFFECT OF RETENTION FORMS ON ACRYLIC BASE SURFACES ON ADHESIVE STRENGTH OF DENTURE RELINER MATERIALS - Prawesthi, Endang; Tirta, Handoko; Rahmaniawati, Rahmaniawati (Faculty of Vocational Studies, Universitas Airlangga, 2021)
Background: Acrylic prosthesis that are used for a long time are often not sticky anymore and easy off. Treatment that can be done is relining, which is resurfacing with new material addition to prosthesis surface in contact with mucosa. One of materials used is denture reliner made of acrylic material (heat and self cured acrylic). The successful use of this reliner material depends on the retention of acrylic base surface. There is some retentions namely bur strokes, ethyl acetate and Al2O3 sandblast. Purpose: To determine effect of retention in form of bur strokes, Ethyl Acetate and Al2O3 sandblast on acrylic bases surface on adhesive strength of reliner denture material. Method: Research using samples in form of acrylic blocks with a length of 80 mm, a large block width of 10 x10 mm and small block of 10 x 8 mm, reliner material thickness is 3 mm. Total of 64 samples were divided into 2 groups based on reliner materials (heat and self) and each group was divided into 4 groups based on treatment (control, bur stroke, ethyl acetat and Al2O33 sandblast). All samples were subjected to tensile test using UTM to obtain tensile strength values. Result: Heat CA tensile strength value was greater than self CA and the two groups were significantly different (p<0.05), while lowest tensile strength value in control group followed by ethyl acetate and largest value in Al2O3 sandblast and almost all groups were significantly different (p<0.05). Conclusion: Heat CA is more adhesive than self CA and retention on acrylic surface is proven to be effective in increasing adhesive strength of acrylic surface against denture reliner.